ANALISIS PENGARUH TUNJANGAN KINERJA DAERAH (TKD), HUMAN RELATION DAN BUDAYA ORGANISASI TERHADAP KINERJA APARATUR SIPIL NEGARA DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI MALUKU - Valentin Manuputty (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
The developed nation need to be supported by adequate resources and also qualified human resources so as to process them. As one of the nations progress movers The Labor and Transmigration Department is required to be able to provide good service. For that will be also required the good performance of civilian state apparatus. To be able to realize it all needs to be given a stimulus that can make civil state apparatus to improve its performance, such as providing local performance allowances according to standards and rules, keeping a good standing of human relation and strengthening the understanding and sense of belonging to organizational culture that become the identity of organization. This research aims to test and analyze influence of of Local Performance Allowances, Human Relation and organization culture on performance of civilian state apparatus based on the formulation of problems. The research method used is Quantitative with the survey type research to explain the relationship between variables and explanatory research to explain the relationship between variables through hypotheses test. Analytical test tool used is multiple regression analysis.Hypotheses were tested by F test method, t test and determination coefficient (R2), the result showed that (1) Local Performance Allowances had a significant positive influence on performance of civilian state apparatus ; (2) Human Relation has a significant positively affect the performance of civilian state apparatus ; (3) Culture Organization has a significant positive effect on performance of civilian state apparatus. There are several implication that can be suggested from this study. Keywords : Local Performance Allowances, Human Relation, Culture Organization and performance of civilian state apparatus.